Expectancy Violations on Perception in the Residential Setting: An Experimental Study - Bakri, Yasmin Nursyabina; Aina, Izzatush Shafa; Alifa, Amira Rasyanda; Ezra, Keshia; Widiyansari, Zharifa Anisa; Srisayekti, Wilis; Ratnasari, Risa Dwi (INSAN Jurnal Psikologi dan Kesehatan Mental, 2023)
Perception is influenced by four factors; beliefs, values, social influence and expectations. Expectations which affect perceptions are divided into two; expectancy violations and expectancy non-violations. There is a difference in reaction time in perception when expectations match and when they do not match with reality. Treatment was given to a group of 78 college students, in the form of giving perceptions and expectations. Within participants post-test only design was used to see the difference in reaction times of the two treatments. Expectancy violations have a significant influence on the perception time of the participants. This can be caused by past experience which formed expectations, as well as the room layout in the partisipants’ own residence.